2019
DOI: 10.1136/bmjopen-2019-033726
|View full text |Cite
|
Sign up to set email alerts
|

What factors contribute to uncontrolled gout and hospital admission? A qualitative study of inpatients and their primary care practitioners

Abstract: ObjectiveTo provide deeper insight into why patients are admitted to hospital with gout and discover potential targets for better disease control.DesignData from semi-structured interviews were analysed using a thematic analysis approach.Participants and settingEleven inpatients from a tertiary institution in the Australian Capital Territory of Australia and their respective general practitioners (GPs) were invited to participate in the semi-structured interviews.ResultsDespite significant pain and disability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Similar themes were also noted in a recent ACT study. 8 A major barrier to effective management appears to be a lack of knowledge and understanding of gout, its treatment, and, when poorly controlled, its potentially severe long-term outcomes. This lack of knowledge was a key barrier emerging from qualitative studies in the UK 22 and New Zealand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar themes were also noted in a recent ACT study. 8 A major barrier to effective management appears to be a lack of knowledge and understanding of gout, its treatment, and, when poorly controlled, its potentially severe long-term outcomes. This lack of knowledge was a key barrier emerging from qualitative studies in the UK 22 and New Zealand.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search revealed that although the high prevalence and increased severity of gout in this population had been welldocumented, [4][5][6][7] little research had looked into their lived experience. A recent Australian Capital Territory (ACT) 8 study had looked at factors contributing to acute flare-ups requiring admission, but did not address long-standing tophaceous disease. A number of studies in New Zealand (NZ) 7,[9][10][11] and the United Kingdom (UK) 12,13 had highlighted gout's impact on such individuals and communities; however, no study had explored this in the Australian healthcare setting.…”
mentioning
confidence: 99%
“…People with gout experience shame in seeking treatment for gout, 96 feel stigmatised that their gout diagnosis is associated with perceptions of dietary and alcohol excess and identify they do not have enough information about gout. 97 …”
Section: Resultsmentioning
confidence: 99%
“…94 Serum urate monitoring allows the dose of medication to be titrated to a target serum urate of below 6 mg/dL (360 μmol/L) in those with symptomatic gout and often below 5 mg/dL (300 μmol/L) in those with features of severe gout such as tophi. 94 Healthcare and workforce considerations People with gout experience shame in seeking treatment for gout, 96 feel stigmatised that their gout diagnosis is associated with perceptions of dietary and alcohol excess and identify they do not have enough information about gout. 97 Approaches that support patient understanding of gout, strengthen primary care and focus on strong Crystal arthropathies Crystal arthropathies Crystal arthropathies relationships between clinician and patient are important in management to enable patients to manage gout and continue urate-lowering therapy.…”
Section: Managementmentioning
confidence: 99%
“…Gout is a kind of in ammatory arthritis caused by the monosodium urate(MSU) crystals deposited in joints and the surrounding soft tissues,which derives from long-standing hyperuricemia [1] .The course of gout include four stages:asymptomatic hyperuricemia,acute gouty arthritis,intercritical gout and chronic gouty arthritis [2] .Patients can suffer signi cantly attack mainly about the joint pain with sudden onset,fever,redness and swelling when acute gout episodes [3] .This process can affect the patient's quality of life seriously,even functional disability,therefore,gout aroused people's attention increasingly.Nevertheless,with the continuous improvement of people's dietary patterns and lifestyle,the prevalence of gout are on the increase remarkable [4] .A large number of epidemiological data showed that the prevalence of gout in the world is about 0.1-10% on average [5][6] .In western developed countries,there are 3-6% of men and 1-2% of women have gout [7] .There is evidenced that [8] the prevalence of gout is more than 1% in Japanese men who older than 30 years,and in China,there might be 2 per 100 inhabitants suffer from gout [9] . At present,the pathogenesis of gout is still in exploration.Previous studies have con rmed that environmental,diet and genetic factors play roles in the development and incidence of gout.For example,vegetarian diet can reduce the risk of gout in Taiwan by Chiu THT et al [10] .And from a genetic standpoint,substantial genome-wide association studies(GWAS), meta-analyses and case-control studies have found that ABCG2,PKD2,SLC2A9,KCNQ1,SLC22A12,SLC17A1,NLRP3 and so on gene polymorphism are in uence the susceptibility of gout [11][12] .Researchers also agreed that genetic factors are the main factors affecting the onset of gout.…”
Section: Introductionmentioning
confidence: 99%